PENERAPAN PUNISHMENT TERHADAP PESERTA DIDIK DALAM KITAB TARBIYATUL AULAD FIL ISLAM - Salamat Pasaribu (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Punishment in the world of education is often carried out by educators, ranging from light punishment to severe punishment, both physical and mental punishment. However, these penalties will have a negative impact on children. Therefore, efforts are made to avoid penalties, especially physical punishment which can endanger students. Punishment in Islamic education is permissible as a demand for and improvement of students' behavior or behavior in a good direction so that they will not repeat mistakes again, as guidance or guidance from an educator towards the students that the correction he has done is an improper act.